TEACHING WRITING NARRATIVE TEXT BY USING COLLABORATIVE LEARNING - Rizki, Indra; Nouvaldi, Deyan; Apsari, Yanuarti (PROJECT (Professional Journal of English Education), 2020)
Writing is an important skill that should  be mastered by English learner. This research deals with teaching writing narrative text by using Collaborative Learning Approach (round table technique) and Scientific Approach. The subjects of this research were X RPL 1 as experimental class and X RPL 3 as control class. Both classes consist of 33 students. The objectives of this research are to know wheter or not the difference between students’ writing ability who were taught by using Collaborative Learning. This research employs the quasi experimental design. The instrument of this ressearch are writing test (pre-test and post test), observation, and interview. The data were analyzed by using statistical product and service solution (SPSS) 25 which through the normality and mann whitney process. The findings showed that the calculation result of gain score showed that the significance value was lower than 0.05 (0.0049 < 0.05) which means there is a difference between students who were taught by Collaborative Learning and those who were taught by using Scientific Approach. Keywords:  Writing, Narrative, Collaborative Learning, Round Table Technique